2006
DOI: 10.1007/s00508-006-0727-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation in Austria: short term quality of life improvements in patients with heart disease

Abstract: These findings provide evidence that the improvements in HRQL and risk factors following cardiac rehabilitation in Austria are clinically important. HRQL should become a standard outcome parameter in cardiac rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
2
12
0
3
Order By: Relevance
“…Many previously published studies demonstrate an improvement in QOL after CR in patients with cardiovascular diseases, although the results came from different models of CR programs (home-based, hospital-based and ambulatory) and different groups of patients. [12][13][14][15][16][17][18][19][20][21][22][23][39][40][41] An improvement in the exercise capacity of CR patients as a result of physical activity similar to our results was also observed in previous studies. 3,5,44,45 We found no correlation between increasing exercise capacity and the improvement in health-related QOL according to EQ-5D and SF36.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many previously published studies demonstrate an improvement in QOL after CR in patients with cardiovascular diseases, although the results came from different models of CR programs (home-based, hospital-based and ambulatory) and different groups of patients. [12][13][14][15][16][17][18][19][20][21][22][23][39][40][41] An improvement in the exercise capacity of CR patients as a result of physical activity similar to our results was also observed in previous studies. 3,5,44,45 We found no correlation between increasing exercise capacity and the improvement in health-related QOL according to EQ-5D and SF36.…”
Section: Discussionsupporting
confidence: 91%
“…Many published studies have revealed improvements in the health-related QOL of patients with CHD after CR programs, either the residential model or ambulatory CR (ACR). [12][13][14][15][16][17][18][19][20][21][22][23] The aim of this study was to evaluate the impact of different models of CR, residential vs ambulatory, on healthrelated QOL according to the exercise capacity of patients with CHD. …”
mentioning
confidence: 99%
“…2). Ein ähnliches System existiert bereits seit längerer Zeit in Österreich und dokumentiert zweifelsfrei die Qualität der kardiologischen Rehabilitation [10]. Die Ergebnisse der stationären Rehabilitation in Österreich sind weitgehend leitliniengerecht und zeigen eine optimale Risikofaktoreneinstellung in der kurzen Betreuungszeit (Tab.…”
Section: Cardiac Rehabilitation In Germanyunclassified
“…Gemäß internationaler Literatur ist die Wertigkeit der Bewegung nicht nur in der Behandlung und Präventi-on von Erkrankungen des Bewegungs-und Stützsys-tems, sondern auch bei Herz-, Kreislauf-, Stoffwechselund psychischen Erkrankungen unbestritten [1][2][3][4][5][6][7][8]. Dem gegenüber steht die zunehmende Bewegungsarmut der durchschnittlichen Bevölkerung in den Industrieländern, hervorgerufen durch vermehrte sitzende Tätigkeiten, Computerarbeit, Auto fahren, Telefonieren, etc.…”
Section: Introductionunclassified